Pelatihan E-Commerce Pada Pelaku Usaha Mikro Kecil Menengah Di Kebon Kosong Jakarta Pusat - Rutinaias Haholongan; Devina Priscillia; Mutiara Sakinah; Revaldo Darmawan; Raihan Hamim Fadillah; Ririn Yustianingsih (Lembaga Pengembangan Kinerja Dosen, 2024)
There are still many UMKM who do not know the existence of e-commerce, and there are still many UMKM who make transactions manually. Currently the emergence of e-commerce has a very positive impact on UMKM and is very helpful in supporting effective and efficient promotion and sales activities. This research aims to find out the influence of e-commerce on the increase in sales of Usaha Mikro Kecil dan Menengah (UMKM). The object of this research is the Zona Warkop in Kebon Kosong, Central Jakarta City. The purpose of this service activity is to introduce and practice e-commerce in the implementation of sales activities, and is expected to develop its creative ideas to balance the lifestyle of the people today. The data collection techniques used include observation, interview, and documentation. The advantage of selling through e-commerce is that it is easily accessible to UMKM through their mobile phones and it is very easy to share photos and videos and provide interesting product descriptions so that consumers are interested.